Exploring the Implementation of Pension Schemes for Expatriates in the UAE - Al Mahmoud, Abdulla (2023)
The UAE has experienced significant economic growth and development, attracting a diverse expatriate workforce worldwide. Expatriates play a crucial role in various sectors of the UAE economy, contributing to its overall prosperity. However, the absence of a dedicated pension system for expatriates has become a pressing concern. Expatriates often need help securing their financial future after retirement due to the lack of a structured retirement savings mechanism. Therefore, this study aims to explore the potential implementation of pension plans that address the unique circumstances of expatriates in the UAE. This study uses a quantitative research method and involves analyzing data from surveys and existing literature on pension systems in other countries to assess the financial feasibility and potential impact of implementing expatriate pension plans in the UAE. The findings of this study shed light on the challenges and opportunities associated with implementing pension plans for expatriates in the UAE.